Enhanced temperature coefficient of resistance of VOX-based uncooled microbolometers manufactured by plasma enhanced atomic layer deposition - Kim, Unjeong; Kim, Dukhwan; Lim, Seokwon; Jeon, Yerin; Kim, Jisu; Lee, Jinchan; Kim, Junmo; Thai Duy, Le; Seo, Hyungtak (Applied Surface Science, 2024)
Vanadium oxide (VOX) is a promising material for developing the sensor film of uncooled microbolometers. However, amorphous VOX film, which is typically formed on the Si substrate, is unstable due to ambient unwanted oxidation in air, making their resistance too high to be employed in microbolometers. Therefore, studies on improving the quality and stability of VOx film are still ongoing. This study presents our strategies based on plasma-enhanced atomic layer deposition (PEALD) and rapid thermal annealing (RTA) for manufacturing VOx films with high crystallization and stability. The VOx sensing layer for microbolometers was fabricated at a low process temperature of 370 °C using NH3 gas, and the rapid thermal anneal was performed as the essential post-deposition annealing process for improving the VOx crystallization. Besides, in-situ deposition of an Al2O3 layer on the VOx film improves its stability. Compared with a bare VOx film, our developed Al2O3/VOx film shows an improvement of −3.5%/K in the temperature range of 298–328 K. For the optimized sample, changes in the electrical, chemical, and surface characteristics of the VOx film due to Al2O3 or Al-doping are studied and discussed in detail to find the mechanism of that improvement.
Keywords: Alumina oxides; Micro-bolometers; Plasma-enhanced atomic layer deposition; Sensor films; Si substrates; TCR; Temperature coefficients of resistance; Uncooled microbolometers; Vanadium oxide films; Vanadium oxides; Alumina oxide; PEALD; TCR; Uncooled microbolometer; Vanadium oxide